2016
DOI: 10.1016/j.psi.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Quality of implementation in an evidence-based family prevention program: “The Family Competence Program”

Abstract: Family prevention programs need to be evidence-based in order to guarantee the success of their implementation. The Family Competence Program (FCP), a Spanish cultural adaptation of the Strengthening Families Program (SFP), has developed different measures and processes to gauge the quality of the implementation. This article is dedicated specifically to two of these measures: the evaluation of the facilitators and the assessment of the family engagement techniques. For evaluating the facilitators, a Delphi te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 11 publications
0
5
0
20
Order By: Relevance
“…• Streghtening Families Program, SFP (Kumpfer & Johnson, 2007) • Programa de Competencia Familiar: Versión Española del SFP (Orte et al, 2018(Orte et al, , 2016(Orte et al, , 2014 • Strengthening Families Program: For Parents and Youth 10-14 (Aalborg et al, 2010;Byrnes et al, 2012; 2018) • Mindfulness-Enhanced Strengthening Families Program 10-14 (MSFP 10-14) (Coatsworth et al, 2018) • Family Matters (FM) (Aalborg et al, 2010;Byrnes et al, 2012) • Incredible Years (Axford et al, 2012;Baker et al, 2011) • Early Risers Conduct Problems Prevention Program (Bloomquist et al, 2012) • Behavioral Parent Training Program (Chacko et al, 2009(Chacko et al, , 2012(Chacko et al, , 2016 • Strategies to Enhance Positive Parenting [STEPP] program (Chacko et al, 2009(Chacko et al, , 2012(Chacko et al, , 2016 • Adolescent Transitions Program (ATP) eb The Family Check-Up (Connell et al, 2007) • Triple P (Eisner y Meidert, 2011;Heinrichs et al, 2005) • Preventive Parent (PT) Training (Garvey et al, 2006) • Bridges to High School Program (Mauricio et al, 2014) • Healthy Families America (HFA) (McCurdy et al, 2006) • Women, Infants and Children (WIC) (Mian et al, 2015) • eHealth Familias Unidas (Perrino et al, 2018) • Early Alliance (Prinz et al, 2001) • Families Program of the Multisite Violence Prevention Project (MVPP) (Quinn et al, 2010) • FRAME-Fatherhood Relationship And Marriage Education (Rienks et al, 2011) • Strong Families program (Ross & DeVoe, 2014) • Coping Power Program (Ryan et al, 2009) Fuente: Elaboración propia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Streghtening Families Program, SFP (Kumpfer & Johnson, 2007) • Programa de Competencia Familiar: Versión Española del SFP (Orte et al, 2018(Orte et al, , 2016(Orte et al, , 2014 • Strengthening Families Program: For Parents and Youth 10-14 (Aalborg et al, 2010;Byrnes et al, 2012; 2018) • Mindfulness-Enhanced Strengthening Families Program 10-14 (MSFP 10-14) (Coatsworth et al, 2018) • Family Matters (FM) (Aalborg et al, 2010;Byrnes et al, 2012) • Incredible Years (Axford et al, 2012;Baker et al, 2011) • Early Risers Conduct Problems Prevention Program (Bloomquist et al, 2012) • Behavioral Parent Training Program (Chacko et al, 2009(Chacko et al, , 2012(Chacko et al, , 2016 • Strategies to Enhance Positive Parenting [STEPP] program (Chacko et al, 2009(Chacko et al, , 2012(Chacko et al, , 2016 • Adolescent Transitions Program (ATP) eb The Family Check-Up (Connell et al, 2007) • Triple P (Eisner y Meidert, 2011;Heinrichs et al, 2005) • Preventive Parent (PT) Training (Garvey et al, 2006) • Bridges to High School Program (Mauricio et al, 2014) • Healthy Families America (HFA) (McCurdy et al, 2006) • Women, Infants and Children (WIC) (Mian et al, 2015) • eHealth Familias Unidas (Perrino et al, 2018) • Early Alliance (Prinz et al, 2001) • Families Program of the Multisite Violence Prevention Project (MVPP) (Quinn et al, 2010) • FRAME-Fatherhood Relationship And Marriage Education (Rienks et al, 2011) • Strong Families program (Ross & DeVoe, 2014) • Coping Power Program (Ryan et al, 2009) Fuente: Elaboración propia.…”
Section: Resultsmentioning
confidence: 99%
“…La evidencia también sugiere que las diferentes actividades realizadas durante las sesiones deben estar bien planificadas y ejecutadas. Entre las diversas técnicas, se consideró que las exposiciones, las discusiones grupales más detalladas y exhaustivas y las actividades grupales conducían a niveles más altos de asistencia de los padres (Orte, Ballester, Vives, & Amer, 2016).…”
Section: Características Asociadas Al Programaunclassified
“…Los resultados obtenidos muestran que las áreas Intrapersonal, Interpersonal y Entorno presentan puntuaciones medias superiores en sus competencias que las relativas a las áreas Desempeño de tareas y Gerencial. Concretamente, en las áreas Intrapersonal e Interpersonal se identifican las puntuaciones medias más elevadas del test, comprendiendo estas dos áreas, de hecho, las principales competencias que necesita el formador de un programa de prevención familiar: la capacidad comunicativa, la capacidad de trabajo en equipo (Orte et al, 2016) y la confianza en sus propias habilidades (Orte et al, 2015). Hay que recordar que el área Intrapersonal, relacionada con la estabilidad emocional, la autoconfianza, la resistencia frente a situaciones adversas y la capacidad de afrontamiento, "el nivel más elevado" obtenido en este estudio se da en la competencia Autoconfianza -referida a cómo los profesionales se sienten con ellos mismos-.…”
Section: Discussionunclassified
“…Estos factores pueden ser considerados y evaluados como variables relevantes en el desarrollo de los programas de prevención. Al mismo tiempo, estos factores podrían ser considerados en la selección de formadores con el fin de afinar y contar con los perfiles más adecuados (Forehand et al, 2010) o también para analizar las necesidades formativas de los profesionales con el fin de mejorar esas habilidades, valores y actitudes favorables al aprendizaje y al cambio (Orte et al, 2016;Small et al, 2009).…”
Section: Introductionunclassified
“…The evaluative research carried out during the last decade has demonstrated the relevance of implementation in the effectiveness of interventions (e.g., García-Poole et al, 2019;Meyers et al, 2012;Orte et al, 2016). Even when we start from evidence-based practices, the results obtained are often below our expectations.…”
Section: Implementation As Coordination Between Stakeholdersmentioning
confidence: 99%